A Case of Fibrous Pseudotumor in the Scrotum: Challenge for Diagnosis and Testicular Preservation - Hirotake Kodama; Shingo Hatakeyama; Teppei Matsumoto; Toshikazu Tanaka; Hirotaka Horiguchi; Yuka Kubota; Hayato Yamamoto; Atsushi Imai; Takahiro Yoneyama; Yasuhiro Hashimoto; Takuya Koie; Chikara Ohyama (Case Reports in Urology)
A paratesticular fibrous pseudotumor is a relatively rare benign disease. Preoperatively diagnosing a fibrous pseudotumor is challenging because distinguishing these masses from malignant tumors on the basis of clinical and radiological findings can be difficult. We present a case of a 28-year-old man who presented with a painless palpable mass in the right scrotum; the fibrous pseudotumor of the tunica vaginalis was treated with organ-sparing surgery. Computed tomography and magnetic resonance imaging revealed paratesticular tumors. Testicular tumor marker levels were within normal limits. We scheduled the patient to undergo tumor biopsy combined with intraoperative rapid diagnosis. Frozen section assessment suggested a fibrous pseudotumor without malignancy. We successfully performed organ-sparing surgery. Testicular-sparing surgery combined with frozen section assessment is primarily used for treating paratesticular fibrous pseudotumors.